Effect of Carboxymethylcellulose and Starch as Thickening Agents on the Quality of Tomato Ketchup - Alam, Md. Khayrul; Ahmed, Maruf; Akter, Mst. Sorifa; Islam, Nurul; Eun, Jong-Bang (Pakistan Journal of Nutrition, 2009)
The objective of this study was to evaluate the effect of thickening agents such as carboxymethylcellulose and starch on the quality parameter of tomato ketchup during storage at 30°C. The carboxymethylcellulose was used at the rate of 0.75-1.25% while, starch was 3-4% in the formulation of tomato ketchup. The moisture content of ketchup was increased by the addition of both the thickening agents. The protein, fibre, ash, acidity and total soluble solid of tomato ketchup were decreased gradually when higher percentage of starch and carboxymethylcellulose were added. Amounts of lycopene, vitamin C and reducing sugar content were higher in the ketchup where starch was used. Starch and carboxymethylcellulose had <10 cfu/g of molds and total viable bacteria throughout storage at 30°C for 60 days. Carboxymethylcellulose treated ketchup was found more suitable than the starch treated through sensory evaluation.